TRADITIONAL WEAPON 'MEKHEMU' AS THE IDENTITY OF THE ALAS TRIBE: SENJATA TRADISIONAL 'MEKHEMU' SEBAGAI IDENTITAS SUKU ALAS - Wati, Ira; Abubakar, Bustami (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
This research discusses the traditional weapon mekhemu as the identity of the Alas tribe in Southeast Aceh Regency. The research method employed includes observation, interviews, and documentation. The results show that the history of mekhemu weapon usage was brought by the Alas Tribe, specifically the Kepale Dese lineage, to the Alas Land, initially in the form of a conventional sharp weapon. The meaning embedded in the handle of the mekhemu weapon symbolizes the declaration of faith, the meaning within the sheath of the mekhemu weapon represents the thirteen pillars of prayer, and the star on the sheath signifies the Four Kings. Mekhemu, as a traditional weapon of the Alas ethnic group, is inseparable from the community's way of life, including in customary marriage practices and circumcision ceremonies within the Alas tribe. Preservation efforts are undertaken by the local government through the implementation, socialization, and widespresad introduction of the mekhemu weapon to the community. Mekhemu is a traditional weapon of the Alas tribe, symbolizing the bravery and honor of a king.